Frailty in mouse ageing: A conceptual approach. (December 2016) - von Zglinicki, Thomas; Nieto, Isabel Varela; Brites, Dora; Karagianni, Niki; Ortolano, Saida; Georgopoulos, Spiros; Cardoso, Ana Luisa; Novella, Susana; Lepperdinger, Günter; Trendelenburg, Anne-Ulrike; van Os, Ronald
Highlights: A broad consensus exists that frailty entails multi-organ dysfunction and increased vulnerability to additional diseases and mortality. The association of the clinical frailty index with mouse age was very similar to that found between the 70-parameter frailty index and age in humans. Quantification of frailty in mouse ageing models, by proper evaluation scales, is key to understand the underlying biology of frailty and ageing. Frailty may be very useful as a simple first indicator and potentially as a screening tool for interventions aimed at improving health span. Abstract: Human life expectancy has increased dramatically in the last century and as a result also the prevalence of a variety of age-related diseases and syndromes. One such syndrome is frailty, which is defined as a combination of organ dysfunctions leading to increased vulnerability to adverse health outcomes. In humans, frailty is associated with various biomarkers of ageing and predicts relevant outcomes such as responses to therapies and progression of health status and mortality. Moreover, it is relatively easy to assess. To foster translation of mechanistic understanding of the ageing process and, importantly, of interventions that may extend healthy lifespan, frailty scales have been reverse translated into mice in recent years. We will review these approaches with a view to identify what is known and what is not known at present about their validity, reproducibility and reliability with a focus on the potential for further improvement.